The ‘Governmental’ betrayal of the sovereign: a legal-anthropological study on neoliberal social inequality and narrative subjectivization among the migrants of Sultanbeyli - Can, Şamil. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2009., 2009)
This anthropological study explores neoliberalism as a concrete way of “conducting” life, rather than a macro-level flux of institutional transformations, or an inaddressable nebula of currently re-organizing global phenomena. Such macrotransformations depend on a wide range of micro-shifts in the concrete daily techniques, practices and means of “survival” which individuals are equipped with in articulating peculiar life-courses. I locate the historical crystallization of such shifts in changes among repertoires of these daily techniques, practices and means of survival, which reflects differing configurations of the Foucauldian triad of sovereignty—discipline—governmentality. On the other hand, I attribute the stakes for “survival” or articulation of “life” to the availability of technologies of narrative subjectivization, which means being “able” to set forth a subjective position in social relations such that it can be articulated as legitimate and meaningful. My research in Sultanbeyli unearths how the current governmental economy of informality is narratively articulated in the form of a position for conducting one’s own conducts against and in the face of liminal openings like social stratification, racial discrimination, and segregation. This “position” is filled in by a concurrent apology for both the governmental economy of informality, and “legitimating” discourses of equalizing historical differences. Nevertheless, this dual position of subjecthood breaks down in moments of addressing the material configurations of social differences. The legitimacy and meaning of narratives are haunted by an “unreal” register of “real differences” crystallizing in a trace that cannot be addressed properly and is hence looped out. In that regard, the success of the governmental economy of informality depends on a narratively displaced failure in addressing this trace. But this precarious displacement leaves the narratively articulated position of subjecthood in havoc: tormented under the grip of an inalienable “trace” to be displaced, it is bound to address it in order to neutralize and equalize it. This ineluctable circle is both the wound and the cure, leaving the social field open for articulating alternative lifecourses for alternative means of survival amidst neoliberalism.
Keywords: Neoliberalism -- Turkey.; Political anthropology -- Turkey.